Perception et pratique de la planification familiale dans le secteur Bambelota.: Etude sociologique auprès des ménages du groupement BONDI-BWILO - LOBWA B., Santhos; Lucien BAITA L.; L., Joseph LOINGO (IJRDO - Journal of Social Science and Humanities Research, 2019)
The access to the domestic scheduling constitutes a fundamental right. The domestic scheduling is crucial for the equality of the sexes and the autonomisation of the women; it is also an essential factor of poverty reduction. About 214 millions women who wish to have resort yet, to methods of efficient domestic scheduling and without danger don’t have the possibility of it because they don’t have access on the news and to the necessary services, or are not sustained by their partner or their community. These women of which the needs in contraceptives are not satisfied live for most in the poorest countries of the world. To widen the range of these services, the UNFPA militates in favor of domestic scheduling policies, guarantees a constant and reliable provision of quality contraceptives, contribute to reinforce the national systems of health and collect some data in order to support his/her/its interventions. Our survey had for objectives to know if the domestic scheduling is known and practiced in the households of BAMBELOTA sector after his/her/its implémentation in the Zone of Health of tutelle(Yabaondo); as to Contribute to the improvement of the married life of the couples of the Bondi-Bwilo grouping through a good sensitization on the domestic scheduling and his/her/its different methods. For that to make, a sampling makes 100 households has been used according to the type in clusters. The results of our survey show that the majority (73%) of our investigated had received no information on the domestic scheduling, and didn’t know service of health in the middle that offers the cares in relation with the PF. It had like consequence the non use of the contraceptive methods by most (69%).